1998
DOI: 10.1111/j.1365-2621.1998.tb15715.x
|View full text |Cite
|
Sign up to set email alerts
|

Flow Properties of Chickpea Proteins

Abstract: Flow properties of aqueous chickpea protein dispersions were investigated. The dispersions had Newtonian flow behavior at concentrations up to 4%. Flow behavior became progressively less Newtonian as concentration increased above 4%. The apparent viscosity of the dispersions was pH and concentration dependent, being higher at the protein's most soluble pHs (pH 2 and 9) and lower at the isoelectric point (pH 4-5). Within the investigated temperatures (15, 25, 35 and 55ЊC), power law constants were unchanged up … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 23 publications
2
11
0
Order By: Relevance
“…Similar results have been reported for starch pastes elsewhere. Liu and Hung (1998) studied the flow properties of chickpea protein. They also found a nonNewtonian behavior when increasing protein or salt concentration.…”
Section: Steady Shear Rheological Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar results have been reported for starch pastes elsewhere. Liu and Hung (1998) studied the flow properties of chickpea protein. They also found a nonNewtonian behavior when increasing protein or salt concentration.…”
Section: Steady Shear Rheological Propertiesmentioning
confidence: 99%
“…Liu and Hung (1998) reported that the chickpea protein dispersion exhibited Newtonian behavior at low protein or salt concentrations. Ahmed et al (2006) studied the thermorheological characteristics of soybean protein isolate.…”
Section: Introductionmentioning
confidence: 99%
“…Knowledge of the rheological behavior of food products is essential for process design and evaluation, quality control, and consumer acceptability (Rao 1977); therefore, information on the flow properties of both native and modified chickpea protein dispersions warrant more investigation. The flow property of native chickpea protein dispersion has been reported in a previous study (Liu and Hung 1998a).…”
Section: Introductionmentioning
confidence: 62%
“…So far, some researchers have studied the functional properties of chickpea protein (Paredes‐López et al. 1991; Liu and Hung 1998a,b; Sánchez‐Vioque et al. 1999; Kaur and Singh 2007; Zhang et al.…”
Section: Introductionmentioning
confidence: 99%
“…(1991) found that nitrogen solubility, oil absorption, emulsion property and foam property of chickpea protein isolated by micellization and isoelectric precipitation technique were compared favorably with those of a commercial soybean protein. Liu and Hung (1998a) investigated the flow properties of chickpea protein and found that chickpea protein dispersions exhibited a Newtonian behavior at low protein concentration or low salt concentration. Sánchez‐Vioque et al.…”
Section: Introductionmentioning
confidence: 99%